In-Office Ultrasound Facilitates Timely Clinical Care at a Multidisciplinary Kidney Stone Center. Issue 3 (30th May 2020) - Sorensen, Mathew D.; Thiel, Jeff; Dai, Jessica C.; Bailey, Michael R.; Dunmire, Barbrina; Samson, Patrick C.; Chang, Helena; Hall, M. Kennedy; Gutierrez, Brianna; Sweet, Robert M.; Harper, Jonathan D.
Abstract: Introduction: A considerable publication record exists comparing sensitivity and specificity of radiological ultrasound (including point of care ultrasound) to computerized tomography for stone disease. However, the practical application of in-office ultrasound to support the growing number of kidney stone centers around the world represents a nuanced topic that is ripe for study and discussion. Methods: We provide a descriptive analysis of how in-office ultrasound is being used as an adjunct to clinical care based on our experience during 50 days in clinic at an institutionally affiliated, multidisciplinary kidney stone center. Clinic subjects gave consent and underwent ultrasound as part of research studies. Ultrasonograms were shared with and verified by the treating physician before the patient was discharged from care. We counted the number of times research imaging altered the care plan. Results: Of the 60 patients enrolled the clinician used the information obtained from the studies in 20 (33%) to determine the course of clinical care that resulted in a change in treatment or process. Conclusions: Ultrasound has the potential to be a cost-effective and valuable tool that can provide more efficient workflow within a kidney stone center or urology clinic.